Exceptional point in a coupled Swanson system. (1st March 2022) - Bagchi, Bijan; Ghosh, Rahul; Sen, Sauvik
Abstract: We propose an interacting non-Hermitian model described by a two-mode quadratic Hamiltonian along with an interaction term to locate and analyse the presence of an exceptional point in the system. Each mode is guided by a Swanson-like quadratic Hamiltonian and a suitable choice is made for the interaction term. The parity-time symmetric transformation is adopted in the standard way relevant for a coupled system.